P09.28 Survey on the data quality of syphilis cases reported in 5 provinces of china. (13th September 2015) - Gong, XD; Yue, XL; Jiang, N
Abstract : Introduction: The results of syphilis surveillance showed that there were some singnicant problems in syphilis stage diagnosis and case-reporting in China. In order to assess the data quality of syphilis case reported in the country, and identify the problems for improving the quality, we conducted this sampling survey. Methods: According to the national protocol and syphilis diagnostic criteria, checking data with original reporting cards, clinical and laboratory logs of syphilis cases reported, assessment of diagnosis correctness were conducted by related experts at 43 medical hospitals/institutions sampled in 13 counties of 10 prefectures in 5 provinces based on geographic distribution to evaluate the data quality, and Excel 2003 and SPSS18.0 software were employed in data analysis. Results: The proportions of the reporting cards timely reported, completely filled, correctly filled, correctly entered by web for syphilis cases were as high as with 99.82% (1691/1694), 97.05% (1644/1694), 96.22% (1630/1694) and 96.22% (1630/1694), respectively, and the one of the reporting cards repeatedly reported was very low with 1.42%(24/1694) in 5 provinces. The proportions of correct diagnosis for syphilis cases was high with 95.40% (2491/2611), however, the ones of correct stage for primary, secondary and latent syphilis were not high with 42.49% (167/393), 77.46% (275/355) and 85.89% (1497/1743), respectively. There was the severe bias of misclassification in primary and secondary syphilis, the reason of which was that some latent syphilis cases were falsely classified into primary and secondary ones by non dermatological/STD and in-patients department doctors. Conclusion: The indicators of data quality related to reporting information and correct diagnosis of syphilis cases were high, however proportion of correct stage for primary and secondary syphilis cases was low, which directly affected on analysis of syphilis incidence. It is urged that the training on related doctors in syphilis diagnosis criteria should be strengthened to substantially improve the data quality. Disclosure of interest statement: No potential conflicts of interest.